KELUARGA METODE LAGUERRE DAN KELAKUAN DINAMIKNYA DALAM MENENTUKAN AKAR GANDA PERSAMAAN NONLINEAR - Een Susilawati; Supriadi Putra; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the family of Laguerre method to find multiple roots of non-linear equations with a known multiplicity. Analytically, we show that this iterative method has a convergence of order three. Furthermore, by choosing the value of certain parameter in the Laguerre method, we obtained several well-known iterativemethods. Using some test functions, we compare the family of Laguerre methods to obtain a root of nonlinear equation by looking at the number iterations of the methods. In addition, comparisons are also made through Basins of Attraction.